Inelastic Neutron Scattering Study of Brønsted Acidity and Water Confinement in Zeolites - Mónica Jiménez-Ruiz; Tetiana Lemishko; Susana Valencia; German Sastre; Fernando Rey (Proceedings, 2019)
Zeolites, crystalline and microporous aluminosilicates, are one of the most important groups of functional materials. [...]